Neopentecostalismo na imprensa escrita brasileira : representações veiculadas no Jornal O Globo (1989-2002) - Souza, Jean Carlos Pereira de (2021)
This work aims to analyze the content published by the Brazilian written press, specifically in the newspaper O Globo, on the theme of Neo-Pentecostalism. In the research process, we collected 182 journalistic pieces of different types (signed articles, columns, notes and reports). The study intends to consider data from the newspaper's history, its characteristics and political-ideological position, especially its religious orientation. As a source of research, we will analyze O Globo's digital collection. Although it does not appear as a central documental set, we also occasionally resort to other printed bodies and to some television productions with a view to subsidizing the discussion on neo-Pentecostalism and media in Brazil. Thus, in addition to being a source, O Globo will be the object of problematizing the relationship between media and religion in contemporary Brazil, especially some aspects that characterize religious disputes and the media market. For the study, the time frame was limited between 1989 and 2002. The year 1989 represents the initial chronological cut as it is the time when TV Record is purchased by the Universal Church of the Kingdom of God and also when this movement starts to be spread more frequently in the newspaper O Globo. Regarding the final point of this cut, we chose 2002, where we have a strong relationship between politics and religion. On the theoretical assumptions, we borrow the concept of Representation from Roger Chartier. Finally, it is noteworthy that the dissertation proposal consists of the presentation of three chapters.